Attathbiqot alfiqhiyyah li Qo'ijdah La Dhororo Wa La Dhiroro fii Taqdimi Wasail Al In 'Asy Liman La Yurja Bur Uhu - Badrudin, Moh; , Dr. Muinudinillaah Basri, MA (2015)
Please be aware that some diseases potentially can not be treated or non-healing in a medical context. And it often makes the doctors decided that this patient will lead to death in a few months, and make these patients really wish that the death relieves their suffering. In this case, everyone should give a special treatment to them, including the hospital, doctors, and even the public, especially the families of patients. To settle this problem, the doctors should have the knowledge and insight into the attitude that should be taken. Surely that in Islam, there are some principles or rules which can be used as ethics to solve this situation. Among these rules are principles that is "There should be no danger and should not harm", it is a part of main principle, and has been agreed by ulama. Every research ought to be ensured to have goals. And this simple research is also has some descriptions of the major and important problems. These problems are as follows : 1. Simplify the guidance for a doctor in providing facilities to recover dispirited patient through the concept offiqh, that is "There should be no danger and should not harm". 2. Describes how a doctor to postulate using the fiqh principles (including rules which are underneath branch) the problem of providing facilities to recover dispirited patient . To achieve this goal, the researcher uses scientific method like the others generally, namely: analytical methods, inductive and descriptive approach. Please from this research show results, and the most important: First, the doctor reassured heart and sure to stop artificial organs from a patient who Aergy hope of recovery by three expert doctors trustworthy decision citing the base do no harm. Second, take this rule (and the rules thereunder) machine can out the disposition of such suspension, arguing that the survival of the patient in this case harm him and his family and to be removed with the knowledge that this rule pay the damage and found inviolable in all its forms.